Surgical Decision Making in Preduodenal Portal Vein: Report of Two Cases in Neonates - Simona Rusu; Ahmad Zaghal; Muhammad S. Choudhry (Georg Thieme Verlag KG, 2018)
Preduodenal portal vein (PDPV) is a rare anomaly that can cause duodenal obstruction. PDPV is associated with other congenital anomalies, mainly cardiac and gastrointestinal. Treatment usually consists of bypassing the obstruction by duodenoduodenostomy. We report two cases of PDPV in association with atrial isomerism and malrotation with different surgical management.